2002
DOI: 10.3354/meps231269
|View full text |Cite
|
Sign up to set email alerts
|

Foraging niches of three Diomedea albatrosses

Abstract: Three species of biennial breeding southern hemisphere albatrosses -Diomedea sanfordi from the Chatham Islands, D. antipodensis from Antipodes Island and D. exulans from South Georgia -were tracked using CLS-Argos satellite system during the 1990s. Harness attachment and duty cycling of transmitters enabled long-term deployments covering both the breeding and nonbreeding ranges. The feeding ranges for breeding birds of each species were different. D. sanfordi foraged over continental shelves to the shelf edge,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 28 publications
2
44
0
Order By: Relevance
“…One exception is the assemblage of marine higher predators in the sub-Antarctic, which contains numerous flying or diving central place foragers with broadly overlapping dietary preferences and breeding chronologies. Efforts to explain how so many ecologically similar species can exist in sympatry have concluded that differences in diet and foraging areas are the most important isolating mechanisms, at least for albatrosses and petrels (Croxall & Prince 1980, Croxall et al 1997, Cherel et al 2002, Nicholls et al 2002, Phillips et al 2005. Satellite tracking has revealed some differences in habitat use at large spatial scales, between species, sexes and breeding stages (Waugh & Weimerskirch 2003, BirdLife International 2004.…”
Section: Introductionmentioning
confidence: 99%
“…One exception is the assemblage of marine higher predators in the sub-Antarctic, which contains numerous flying or diving central place foragers with broadly overlapping dietary preferences and breeding chronologies. Efforts to explain how so many ecologically similar species can exist in sympatry have concluded that differences in diet and foraging areas are the most important isolating mechanisms, at least for albatrosses and petrels (Croxall & Prince 1980, Croxall et al 1997, Cherel et al 2002, Nicholls et al 2002, Phillips et al 2005. Satellite tracking has revealed some differences in habitat use at large spatial scales, between species, sexes and breeding stages (Waugh & Weimerskirch 2003, BirdLife International 2004.…”
Section: Introductionmentioning
confidence: 99%
“…The divergence of behavioural, ecological and morphological traits (e.g. Lequette and Jouventin 1991;Prince et al 1997;Nicholls et al 2002) during separation may be sufficient to maintain effective isolation during secondary contact. However, in the case of T. impavida and T. melanophrys it appears likely that the period of separation was not prolonged enough for reproductive isolation to occur (cf.…”
Section: Black-browed-type Albatrossesmentioning
confidence: 99%
“…On the other hand, plastic also tends to accumulate over the shelf-break and continental shelf areas of the southwest Atlantic because of the density of fishing vessels, the main source of marine debris for seabirds in the region Quintana 2003, 2008), and the occurrence of numerous oceanographic fronts (Acha et al 2004). This may at least partially explain the greater frequency of plastic in royal albatrosses, which forage extensively over the continental shelf and shelf-slope (Nicholls et al 2002;JimĂ©nez et al 2014) and interact with large number of fishing vessels, including trawlers, longliners and others, mainly off Uruguay and Argentina (Favero et al 2011;JimĂ©nez et al 2014). However, it is also probable that some of birds sampled in our study had retained plastic particles in their ventriculus from the Pacific Ocean.…”
Section: Discussionmentioning
confidence: 96%
“…Wandering and Tristan albatrosses breed in South Georgia and Tristan da Cunha, respectively, and both breeding and nonbreeding birds use the southwest Atlantic; Wandering albatrosses forage over an extensive region from oceanic waters to the shelf break, whereas Tristan albatrosses forage almost exclusively in oceanic waters in the subtropical region (Nicholls et al 2002;Cuthbert et al 2005;Reid et al 2013). The reported plastic accumulation area for the subtropical south Atlantic gyre (CĂłzar et al 2014;Ryan 2014) matches very well with the distribution of Tristan albatross, at least during breeding, suggesting a greater susceptibility in this species to plastic ingestion.…”
Section: Discussionmentioning
confidence: 99%